Revision of Mesitiinae (Hymenoptera, Bethylidae) from Madagascar, with description of eleven new species - Barbosa, Diego N.; Azevedo, Celso O. (Zootaxa, 2012)
Thirteen species of Mesitiinae from Madagascar are recognized. Pilomesitius madagascarensis Móczár, Zimankos madagascarensis (Móczár), and eleven new species: Anaylax betsileo Barbosa & Azevedo, sp. nov., A. mahafaly Barbosa & Azevedo, sp. nov., Clytrovorus bara Barbosa & Azevedo, sp. nov., C. merina Barbosa & Azevedo, sp. nov., C. zafimaniry Barbosa & Azevedo, sp. nov., Codorcas antanosy Barbosa & Azevedo, sp. nov., Itapayos antaimoro Barbosa & Azevedo, sp. nov., Itapayos mikea Barbosa & Azevedo, sp. nov., Pycnomesitius tanala Barbosa & Azevedo, sp. nov., Zimankos makoa Barbosa & Azevedo, sp. nov., Z. sakalava Barbosa & Azevedo, sp. nov. One new combination is proposed: Zimankos madagascarensis Móczár 1970, comb. nov. from Sulcomesitius with the discovery of its male. A key of Malagasy Mesitiinae species are provided.